First two bilateral hand transplantations in India (Part 1): From vision to reality - Iyer, Subramania; Sharma, Mohit; Kishore, P.; Mathew, Jimmy; Vijayaraghavan, Sundeep; Ramu, Janarthanan; Wakure, Abhijeet; Reddy, Raghuveer; Mali Chetan, S. M.; Varma, Visakh; Chaudhari, Ashish; Dhake, Swapnil; Omkumar, Akshay; Prasad, V. G. (Indian Journal of Plastic Surgery, 2017)
Introduction: Vascularized composite tissue allotransplantation is a relatively new concept, which was unavailable in the Indian subcontinent till a bilateral hand transplant was carried out successfully in January 2015. Materials and Methods: The setting up of the transplant programme involved obtaining legal clearances, creating public awareness, harnessing the institutional facilities, drawing up protocols, assembling the surgical team, managing immunological issues, rehabilitation and preparing the ancillary services. Results: Both, the first and second bilateral hand transplants were resounding successes with both the recipients getting back to their original daily routines. Conclusions: The organisation of the hand transplant programme was a large task, which necessitated intensive planning, and cooperation from various teams within and outside the institution. Exemplary team-work was the key to the phenomenal success of these path breaking endeavors in the subcontinent.
Keywords: Composite tissue allotransplantation; first coloured hand transplantation; India's first hand transplantation; vascularised tissue allotransplantation